Keberhasilan Inisiasi Menyusu Dini, Involusi Rahim, Pelepasan Plasenta dan Perdarahan Kala IV Persalinan - Astuti Setiyani; Nana Usnawati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Early initiation of breastfeeding can reduce postpartum hemorrhage. This study aims to analyze the relationship between the success of early initiation of breastfeeding with uterine involution, placental separation and prevention of bleeding in the fourth stage of labor. The design of this study was cross-sectional. The sample in this study was 100 mothers who gave birth at the “W” Midwife Independent Practice, Magetan from April to August 2018, who were selected using a simple random sampling technique. Data were collected through observation, then analyzed by logistic regression test. The results showed that there was a relationship between the success of early initiation of breastfeeding with uterine involution, placental separation and the amount of bleeding in the fourth stage of labor. Keywords: early initiation of breastfeeding; uterine involution; detachment of the placenta; bleeding in the fourth stage of labor ABSTRAK Inisiasi menyusu dini dapat mengurangi perdarahan post partum. Penelitian ini bertujuan untuk menganalisis hubungan antara keberhasilan inisiasi menyusu dini dengan involusi rahim, pelepasan plasenta dan pencegahan perdarahan pada persalinan kala IV. Desain penelitian ini adalah cross-sectional. Sampel dalam penelitian ini adalah 100 ibu bersalin di Praktek Mandiri Bidan “W”, Magetan pada bulan April sampai Agustus 2018, yang dipilih dengan teknik simple random sampling. Data dikumpulkan melalui observasi, lalu dianalisis dengan uji regresi logistik. Hasil penelitian menunjukkan adanya hubungan antara keberhasilan inisiasi menyusu dini dengan involusi rahim, pelepasan plasenta dan jumlah perdarahan Kala IV persalinan. Kata kunci: inisiasi menyusu dini; involusi rahim; pelepasan plasenta; perdarahan kala IV persalinan